A study of the spectral reflectivity of the osmanthus tree leaf and its spectral properties. (September 2022) - Jian-Feng, Luo; Chang-Qing, Xie; Shu-Lin, Pan; Chuan-Lin, Tang; Wang, Chen; Hong-Liang, Yi; He-Ping, Tan
Highlights: A reflectivity model of multi-layer semitransparent composite is established. The ray-tracing method is used to trace radiative energy within the composite. The interfaces of the composite are semitransparent and diffuse reflection. The spectral reflectivities of multi-layer osmanthus tree leaves are measured. The absorption coefficient and refractive index of osmanthus leaf are fitted out. Abstract: In the forest canopy, reflection of solar energy and photosynthesis contribute to the greenhouse effect and our living environment. A multi-layer leaf reflectivity model was established using the ray-tracing method to study the spectral properties of an osmanthus tree leaf with assuming the tree leaf surface to be diffuse reflecting. A spectrophotometer has measured the spectral reflectivity of one to five-layer leaf composites. The spectral refractive index and absorption coefficient of the leaf has been found by inversion fitting using the reflectivity model of the leaves. Our study shows that the law of its spectral refractive index is consistent with the change of spectral reflectivity with wavelength. The evolution of its spectral absorption coefficient with wavelength is contrary to the shift in its spectral reflectivity. This method can be extended to measure other semitransparent media's spectral absorption coefficient and refractive index.